Health attitude and perception towards consumption of fish / Joachim Engan Sigau - Engan Sigau, Joachim (2009)
Studies had been done to prove that physical and sensory properties (bones, smell and taste), together with price, availability, convenience, as well as personal involvement, interest in health and nutrition are important factors that influence seafood consumption behavior in general, and fish consumption in particular (Juhl and Poulsen, 2000; Leek et al, 2000; Olsen, 2003; Olsen et al, 2007; Schoderer and Grunert, 2001; Trondsen et al., 2003, 2004; Verbeke and Vackier, 2005). The image of fish among consumers is predominantly healthy and attitudes towards eating fish are strongly favorable (Olsen, 2003; Trondsen et al., 2004). Fish is beneficial to human health, as it is an important source of a number of nutrition, particularly protein, retinol, vitamin D, vitamin E, iodine, selenium and the essential long-chain polyunsaturated fatty acid. On the other hand, fish may include contamination with pathogenic bacteria, viruses, toxins, chemical and other environmental hazard (Sumner and Ross, 2002). Recently, several studies concentrated on the question whether it is possible to follow the dietary recommendations of eating two portion of fish a week, of which one should be fatty fish, without exceeding tolerable intakes of chemical contaminants (Mpzaffarian and Rimm, 2006; Sioen et al 2008, b;Smith and Sahyoun, 2005. The result showed that health benefits of eating fish outweigh the potential risks. Despite conclusive evidence about the content and positive effect of omega-3 fatty acid in fish, and consumer awareness and beliefs about the fact that fish content omega-3 fatty acids and that this nutrients are beneficial for human health were found to be rather poor (Verbeke et al, 2005).